SCHEDULE OF MAKING COURSE COLLEGE APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 - Ahmad Sofyan; Sahni Damerianta P, SKom, MMSI (Jurnal Sistem Informasi, 2001)
Scheduling problems in a college of great importance, if the scheduling is still using the old fashioned way, manually. Manual operation is not efficient, scheduling courses conducted by universities can be facilitated by using computer facilities, in conducting these activities. In the operating schedule in a college course would be watered down as to save time in filling the schedule courses, and not the similarity of time that can interfere with the teaching and learning system. So from the application of computer use in the operation of a scheduling can solve complex problems in data storage that will further save cost and time efficiently. The author discusses in this keesempatan about making a complete schedule to complete the course with similar problems the same time by the faculty and within hours the same as using Microsoft Visual Basic 6.0.